Monoclonal anti-CD38 therapy in human myeloma: retrospects and prospects - Alberto L. Horenstein; Angelo C. Faini; Angelo C. Faini; Fabio Morandi; Erika Ortolan; Paola Storti; Nicola Giuliani; Nicola Giuliani; Paul G. Richardson; Fabio Malavasi; Fabio Malavasi (Frontiers in Immunology)
Monoclonal antibody therapy using CD38 as a target remains central to managing human multiple myeloma (MM). CD38 was selected early on as a target for mAb-mediated therapy for MM, driven by findings from an early Cluster of Differentiation (CD) Workshop. The first CD38-targeting antibody to be approved yielded strong trial results, significantly improving survival rates and earning widespread patient acceptance. However, resistance to the therapy later emerged, complicating treatment management. Despite CD38’s still central role in MM therapy, too little attention has been paid to its broader roles–not only as a myeloma marker but also as an enzyme and adhesion molecule in physiology. This review, a collaborative effort between basic scientists and clinical experts, explores some of the lesser-known mechanisms of antibody action and interactions with CD38 at key stages of treatment. The review also highlights the relevance of the MM environment, focusing on the importance of the bone marrow (BM) niche. The goal is to identify new agents whose unique properties may enhance tumor eradication. By gaining a deeper understanding of interactions between therapeutic antibodies, myeloma cells, and the tumor microenvironment (TME), it is hoped that previously unrecognized vulnerabilities within the disease may be revealed, paving the way to more effective treatment strategies.